KONVERSI LUMPUR AKTIF MENJADI BIODIESEL DENGAN PROSES SUBKRITIS TANPA KATALIS SECARA INSITU - Gunawan, Farrel; Gunawan, Iwan; Palinggi, Sarah Yarden; Ayucitra, Aning; Ismadji, Suryadi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Nowadays, biodiesel has been produced commercially for partial supporting energy demmand in Indonesia. However, high price feedstock and need of catalyst appear as the problem. In this research, activated sludge which is available as large scale waste and comprises significant ammount of lipid fraction (direct adsorption of industrial waste water and microbial lipid), was converted into biodiesel using subcritical process (without catalyst). The potential of the feedstock and process in producing biodiesel were studied. The optimum condition of the production is 215oC, 65 bar, and 5:1 of methanol to lipid mass ratio and the biodiesel meets the SNI-04-7182-2006 spesification.Â Keywords: biodiesel, green process, activated sludge